2015
DOI: 10.1016/j.otsr.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dual mobility cup in revision total hip arthroplasty: Dislocation rate and survival after 5 years

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…After reviewing the abstracts of these, 75 were screened for eligibility and 16 were identified for inclusion. Fifty-nine articles were excluded because reporting no IPD episodes (30 articles) [7] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , IPD episodes were not mentioned (13) [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , reporting delayed IPD episodes (13) [8] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , reporting early IPD episodes with old DM designs with small femoral heads (2) [9] , [69] , and reporting a suspicious IPD episode (1) [70] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the abstracts of these, 75 were screened for eligibility and 16 were identified for inclusion. Fifty-nine articles were excluded because reporting no IPD episodes (30 articles) [7] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , IPD episodes were not mentioned (13) [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , reporting delayed IPD episodes (13) [8] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , reporting early IPD episodes with old DM designs with small femoral heads (2) [9] , [69] , and reporting a suspicious IPD episode (1) [70] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…24 5- and 10-year survivorship data on dual-mobility cups have shown that a reduced risk of postoperative complications with similar 5 year outcomes when compared to other treatment methods makes DMC-THA the overall most cost-effective treatment long-term despite the initial high cost of the implant. 23,24,7476…”
Section: Discussionmentioning
confidence: 99%
“…Mean HHS improved preoperatively from 60 to 85 at latest followup. Several studies have reported reliable results and outcomes with the use of DM constructs in primary and revision THA [8,20,25]. In a series of 36 patients undergoing revision THA considered at high risk for recurrent dislocation, Plummer et al [16] reported improved HHS by a mean of 45 points with a final mean of 90.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report indicated that cumulative risk of redislocation after revision THA for recurrent instability was 35% at 15 years [10]. There are multiple surgical options to address an unstable prosthesis including abductor repairs or reconstructions, conversion to hemiarthroplasty [15], large-diameter femoral heads [1,19,26], acetabular revision [18], increased hip offset [18], constrained liners [4-7, 9, 13, 19, 24], and dual-mobility (DM) constructs [3,8,12,16,17,20,21,24,25]. One of the more commonly utilized techniques to treat or prevent recurrent dislocation, especially in multiply operated on patients with deficient abductor mechanisms, is constrained liners [4-7, 9, 13, 19, 23].…”
mentioning
confidence: 99%